RESISTANCE AGAINST THE AUTHORITARIANISM OF THE EGYPTIAN REGIME IN THE NOVEL MUZAKKARAT FI SIJN AL-NISA’ BY NAWAL AL-SA’DAWI - Sindy Febrianisa; Muhamad Nazar; Siti Karomah; Asrina Asrina (Faculty of Humanities UIN Maulana Malik Ibrahim Malang, 2025)
This research aims to reveal the factors that led to the public's resistance against the Egyptian authorities in the novel Muzakkarat Fi Sijn al-Nisa’ by Nawal El Saadawi. The issues presented in the novel are related to the inconsistency of the Egyptian authorities in implementing the democratic system they claimed to uphold, which in turn provoked resistance from the people. This study is a library research using a qualitative approach. The data in this study consist of words, phrases, and sentences related to the people’s resistance against the Egyptian authorities in the novel. The data collection technique in this research was carried out through library research, as the main source of data comes from literary texts. The data analysis technique in this study employs the dialectical method, which seeks to integrate two theoretical frameworks Alan Swingewood’s sociology of literature and James C. Scott’s theory of resistance to achieve a comprehensive understanding of the social phenomena represented in the literary text. The results of this study indicate that there are two forms of resistance carried out by the people against the Egyptian authorities: open resistance and hidden resistance. Furthermore, the resistance stems from three main factors: authoritarian governance, human rights violations, and social injustice perpetrated by the Egyptian authorities.